PERMASALAHAN MADRASAH ERA OTONOMI DAERAH - Umul Hidayati (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractA fundamental problem faced by madrasahs in the era of global economy is with the position of madrasah in the governmental structure. Structurally, madrasash is a vertical agency without being autonomous-structured but operationally madrasah is within the office of local government (city/regency). Such a condition has implications to the policy of local government that unlikely to favor madrasah. The policies of local government concerning empowering madrasahs can be clasified into four attitudes: 1) in favor of madrasah that meant local goverment has proportionally paid attention to and cared for the madrasah; 2) lack of supporting madradah taht meant though local government has paid attention to the madrasah, such an sttention was discriminative in character among the madrasahs and schools; 3) doubt in character that meant local government has had a willingness to pay their attention to the madrasah, but they were afraid of violating rules; and 4) not in favor of madrasah that meant were no any attentions and treatments at all given by local government to madrasah wheter in form of finance, staff, facility and infrastructure of curriculum.